PREFERENSI FAKTOR – FAKTOR MOTIVASI KERJA PNS DI DIREKTORAT ZENI ANGKATAN DARAT, JAKARTA - Firman, Galang Nuzul; Lataruva, Eisha (Diponegoro Journal of Management, 2014)
There  are  5  motivation factors  examined in  this  study are  the  factors  of  leadership,compensation (salary  and  benefits),  the relationship  between co-workers, career  development, appreciation  from  organization.  The sample  in  this  study is  the  organization's  Civil Service Direktorat Zeni Angkatan Darat, East Jakarta,  which amounts to 74 employees. The analysis used in this study is the Spearman Rank Correlation Test, Test of Non - Parametik Mann Whitney and Kruskall Wallis test and Duncan test.The results showed that the preferences of motivational factors in the organization DITZIAD civil servants from the first  to the fifth rank is: Leader Factor,  Factor  Compensation (salary  and  benefits),  the  relationship  between co-workersfactor,  Career  Factor,  and  Factor appreciation. There are five factors correlations significant motivation to work among employees with different gender. There are significant differences between male officers and female officers in assessing the factor of appreciation. Male and female employees alike choose factors as the leader of  the main factors that  can  motivate them to work. Based on class  rank,  showed significant differences in the career development factors. Employees with the stratification according to rank≥ IIIC preferred career  development factors as the most motivating factor, while employees with the stratification according to rank IIIA-IIIB, IIC-IID, IIa-IIb prefer as leader of the main factorsthat motivate them to work.